2016
DOI: 10.1007/s40617-016-0148-6
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Stimulus Presentation and Size on Preference

Abstract: The impact of stimulus size and presentation on choice during a preference assessment was investigated using a modified multiple-stimulus without replacement (MSWO) technique. Stimuli were either presented with a uniform magnitude, as determined by mass, or in a manner consistent with caregiver report of reinforcer consumption. While both assessment procedures identified the same top three preferred items in three out of five cases, greater variability in the preference rank of less preferred items was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…However, if an individual does not display certain discrimination or matching skills, these modalities may affect results of the SPA (e.g., Brodhead et al, 2016; Clevenger & Graff, 2005; Conyers et al, 2002). Further, various stimulus dimensions, such as the magnitude of the stimulus (e.g., number of edibles; Hoch et al, 2002; Moore et al, 2017; Trosclair‐Lasserre et al, 2008) and duration of stimulus access (Clark et al, 2019; DeLeon et al, 1999; Hoffman et al, 2017; Jones et al, 2014; Steinhilber & Johnson, 2007) have been shown to influence results of preference assessments.…”
mentioning
confidence: 99%
“…However, if an individual does not display certain discrimination or matching skills, these modalities may affect results of the SPA (e.g., Brodhead et al, 2016; Clevenger & Graff, 2005; Conyers et al, 2002). Further, various stimulus dimensions, such as the magnitude of the stimulus (e.g., number of edibles; Hoch et al, 2002; Moore et al, 2017; Trosclair‐Lasserre et al, 2008) and duration of stimulus access (Clark et al, 2019; DeLeon et al, 1999; Hoffman et al, 2017; Jones et al, 2014; Steinhilber & Johnson, 2007) have been shown to influence results of preference assessments.…”
mentioning
confidence: 99%